DIFFERENCE IN SETTING TIME AND WORKING TIME INTERVAL OF CONVENTIONAL ZINC PHOSPHATE CEMENT AND NANOPARTICLE ZINC PHOSPHATE CEMENT (Research report) - Chandra Sari Kurniawati; Delvi Fitriani; Sheila Ananda Putri (Dentino : Jurnal Kedokteran Gigi, 2019)
Introduction: Zinc phosphate cement is one of cavity base material frequently used for pulp protection in the field of dentistry. This material demonstrates superiority in mechanical resilience and manipulation simplicity yet inducing pulp irritation as the reflection of high level acidity. Utilizing nano-particle ZPC may vanquish the shortcoming in conventional mechanical properties. However, brief setting time in nano-particle ZPC will generate higher exothermic reaction accompanied by the shortening of working period. Purpose: To assess the difference in setting time and working time interval of conventional ZPC and nano-particle ZPC. Methods: It is a true experimental laboratory study with post-test control group design. Four treatment groups were presented in five respective repetitions, comprising one scoop (0.318 gr) of conventional ZPC with three drops liquid in Group I, one scoop (0.386 gr) of nano-particle ZPC with four drops liquid in Group II, one scoop (0.386 gr) of nano-particle ZPC with three drops liquid in Group III, and one scoop (0.386 gr) of nano-particle ZPC with two drops liquid in group IV. ZPC was then manipulated in circular motion from powder to liquid. The setting time and working time was determined using stopwatch in second unit which then statistically analyzed using one-way ANOVA and post hoc Tukey HSD test. Result: Nano-particle ZPC with two drops liquid (Group IV) exhibited the shortest setting time value (mean 96.60s) which unveiled concurrently with the briefest working time interval (mean 34s). The longest setting time was presented in conventional ZPC (Group I) in the average of 627.80 seconds which also depicted the lengthiest working period with 84.20 seconds average. Statistical analysis revealed significant disparity in setting time value of conventional ZPC and nano-particle ZPC in each treatment group (p<0.05) while no significant difference was identified in working time data analysis (p>0.05). Conclusion: There is a significant difference in setting time and working time interval of conventional ZPC and nano-particle ZPC.